RANAH KOGNITIF, AFEKTIF DAN PSIKOMOTORIK SEBAGAI OBJEK EVALUASI HASIL BELAJAR PESERTA DIDIK - Zainudin, Zainudin; Ubabuddin, Ubabuddin (Program Studi Pendidikan Agama Islam STIT al Urwatul Wutsqo Bulurejo Jombang, 2023)
The cognitive, affective and psychomotor domains as objects of evaluating student learning outcomes are very important. This study is a literature study with documentary data collection methods and analysis using content analysis. The results of the study stated: Evaluation is an assessment of student learning completeness. Student learning outcomes can be measured using 3 domains namely cognitive, affective and psychomotor aspects. Where the three domains are included in the scope of learning evaluation in the perspective of the learning outcomes domain. In addition to the domain of learning outcomes, there are two perspectives used in the assessment, namely the learning system perspective and the class-based assessment perspective. In the learning system perspective, it consists of; Learning program (objectives, materials, methods, media, and so on), Implementation of learning (activities, teachers, and students), Learning outcomes (short term, medium and long term). while the perspective of class-based assessment is an assessment carried out by the teacher in the context of the learning process. Instruments commonly used are performance appraisal, attitude, written, product project, portfolio, and self-introduction.